Peningkatan Penyembuhan Luka dan Stabilitas Glikemik pada Pasien Diabetes Melitus Tipe 2 dengan Fasciitis Nekrotikan: Laporan Kasus: Improvement in Wound Healing and Glycemic Stability in a Patient with Type 2 Diabetes Mellitus and Necrotizing Fasciitis: A Case Report - Xavier, Julieta de Carvalho; Luruk, Ricardo Correia; Bangun, Argi Virgona; Marpaung, Lilis Suryani (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disease that frequently leads to serious complications, including severe soft tissue infections such as necrotizing fasciitis. Chronic hyperglycemia contributes to impaired tissue perfusion, decreased immune response, and delayed wound healing, thereby increasing the risk of severe infection and poor clinical outcomes. This case report describes the implementation of comprehensive nursing care for a patient with Type 2 Diabetes Mellitus complicated by necrotizing fasciitis. This study employed a descriptive case report design involving a 72-year-old male patient diagnosed with necrotizing fasciitis of the left lower extremity, accompanied by Type 2 Diabetes Mellitus and systemic complications. Nursing care was delivered using the nursing process approach, including assessment, nursing diagnosis, planning, implementation, and evaluation. The main nursing variables addressed were skin/tissue integrity, infection risk, and blood glucose stability. Data were collected through patient interviews, physical examination, wound observation, blood glucose monitoring, and review of medical and nursing records. The primary nursing diagnoses identified were impaired skin/tissue integrity, risk of infection, and unstable blood glucose levels. Nursing interventions focused on aseptic wound care, glycemic control management, infection prevention, pain management, and patient education. Evaluation outcomes demonstrated improvement in wound condition, reduced purulent exudate, stabilization of blood glucose levels, and decreased pain intensity during the course of nursing care. This case report indicates that comprehensive and evidence-based nursing care, particularly strict glycemic control combined with appropriate wound management, plays a critical role in supporting wound healing and preventing further complications in patients with Type 2 Diabetes Mellitus and necrotizing fasciitis.